The effect of high training stress on each of concentration (Blood- urine) on Iraqi national team weightlifters - Yasser, Omar Khalid; Saeed, Taiseer Ahmed; Fenjan, Falih Hashim (International Journal of Psychosocial Rehabilitation, 2020)
The researchers assume that there is no statistically significant relationship on the albumin concentration and turnover of the Iraqi quartet. High intensity training results in a slight increase in blood albumin concentrations. High intensity training only slightly increased the concentration of the albumin. The continuous training for a period of five days in one week leads to an increase in the albumin concentration in the blood and urine. We recommend that similar research be conducted into indicators of kidney and liver function. We also recommend that you take the necessary rest between exercises and between training units to restore full recovery to working muscles. We recommend that you drink adequate quantities of water and other fluids, which must contain carbohydrates or sugars, mineral salts. Such as sodium and potassium to provide the body with energy or calories lost during training and to compensate for the sweating associated with training.